Pengaruh Kompetensi Pedagogik Guru PAK terhadap Motivasi Belajar Siswa Kelas VIII SMP Negeri 4 Doloksanggul Tahun Pembelajaran 2024/2025 - Delima Sarmalija Sidabutar; Grecetinovitria M. Butar Butar; Raikhpoor Raikhpoor; Limmarten Simatupang; Adiani Hulu (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The study aims to determine whether there is a positive and significant influence of the pedagogical competence of PAK teachers on the learning motivation of class VIII students of SMP Negeri 4 Doloksanggul in the 2024/2025 Academic Year. The research hypothesis is that there is a positive and significant influence of the pedagogical competence of PAK teachers on the learning motivation of class VIII students of SMP Negeri 4 Doloksanggul in the 2024/2025 Academic Year. The quantitative research method is descriptive and inferential. The population of all class VIII students of SMP Negeri 4 Doloksanggul in the 2024/2025 Academic Year who are Protestant Christians is 116 people. The sample is random (random sampling), namely 35% from each class of 41 people. The research instrument is a closed questionnaire. The results of the data analysis obtained: a) The value of r count = 0.661> r table = 0.308 and t count = 5.501> t table = 2.02269 indicates a positive and significant relationship between the pedagogical competence of PAK teachers and the learning motivation of class VIII students of SMP Negeri 4 Doloksanggul in the 2024/2025 Academic Year. b) Regression equation. c) Determination test shows that the magnitude of the influence is 43.69%. d) Hypothesis test obtained F count = 30.372> F table = 3.23 then H0 is rejected and Ha is accepted. The study concludes that there is a positive and significant influence between the pedagogical competence of PAK teachers on the learning motivation of class VIII students of SMP Negeri 4 Doloksanggul in the 2024/2025 Academic Year.